Effect of the Fermentation Broth of the Mixture of Pueraria lobata, Lonicera japonica, and Crataegus pinnatifida by Lactobacillus rhamnosus 217-1 on Liver Health and Intestinal Flora in Mice With Alcoholic Liver Disease Induced by Liquor - Wang, Ting; Wang, Zhe; Yang, Zhipeng; Cui, Xin; Yan, Liang; Xu, Zhenshang; Liu, Xinli (Frontiers in Microbiology, 2021)
In this work, we discovered a new fermentation broth that can prevent and regulate alcoholic liver disease (ALD) and intestinal flora, which fermented the mixture of Pueraria lobata, Lonicera japonica, and Crataegus pinnatifida by Lactobacillus rhamnosus 217-1. The contents of polyphenols, puerarin, total isoflavones, and amino acids were significantly increased. Animal experiments showed that the fermentation broth could improve the liver indexes of ALD mice model, increase the activity of superoxide dismutase and glutathione in liver tissue, and reduce the level of malondialdehyde (MDA). Furthermore, the fermentation broth can reduce the levels of serum lipopolysaccharide (LPS), inflammatory factors interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α). Importantly, intestinal flora analysis showed that the fermentation broth could increase the abundance of Lactobacillales and reduce the production of Gram-negative bacteria, thereby reducing the abnormal increase in bacterial diversity caused by alcohol. In conclusion, we may have discovered a new functional food raw material with great application potential. The above findings indicate that the fermentation broth can actively regulate the intestinal flora and improve liver inflammation. The underlying mechanism might be that the fermentation broth could enhance intestinal permeability and reduce the inflammatory signals and LPS transmitted through the gut-liver axis, thereby reducing the oxidative stress and inflammation of the liver caused by alcohol.